The Role of Myeloid-Derived Suppressor Cells in Patients with Solid Tumors: A Meta-Analysis - Zhang, Shuo; Ma, Xuelei; Zhu, Chenjing; Liu, Li; Wang, Guoping; Yuan, Xia (PloS one, 2016)
Targeting immune cells or factors are effective for patients with solid tumors. Myeloid-derived suppressor cells (MDSCs) are known to have immunosuppressive functions, and the levels of MDSCs in patients with solid tumor are assumed to have prognostic values. This meta-analysis aimed at evaluating the relationship between MDSCs and the prognosis of patients with solid tumors. We searched articles in PUBMED and EMBASE comprehensively, updated to March 2016. Eight studies with 442 patients were included in the meta-analysis. We analyzed pooled hazard ratios (HRs) for overall survival (OS), disease-free survival (DFS) and progression-free survival (PFS). The results showed that MDSCs were associated with poor OS (HR, 1.94; 95% confidence interval [CI], 1.42-2.66; P < 0.0001) in patients with solid tumors. PFS/RFS (HR, 1.85; 95% CI, 1.16-2.97; P = 0.01) also indicated the association between MDSCs and prognosis. The HRs and 95% CIs for OS in Asian and non-Asian patients were 2.53 (95% CI 1.61-3.42, p < 0.00001) and 1.67 (95% CI 1.14-2.46, p < 0.0001), respectively. We further analyzed the data according to tumor types. The combined HRs and 95% CIs for OS were 1.26 (95% CI 1.10-1.44, p = 0.0003) for gastrointestinal (GI) cancer, 2.59 (95% CI 1.69-3.98, p < 0.0001) for hepatocellular carcinoma (HCC) and 1.86 (95% CI 1.26-2.75, p = 0.002) for other tumor types. In conclusion, MDSCs had a fine prognostic value for OS and PFS/RFS in patients with solid tumors. MDSCs could be used as biomarkers to evaluate prognosis in clinical practice.